Method for dose assessment to workers and public as a result of inhalation intake of radionuclides during fires at the territories with a high level of radioactive contamination - Zhukova, Olga; Kliaus, Viktoryia; Huseinava, Dziyana; Babich, Alena (Journal of the Belarusian State University. Ecology, 2023)
This article presents a method for estimating exposure doses for persons participating in firefighting and the public as a result of inhalation intake of radionuclides in emergency situations (forest fires) in areas with a high level of radioactive contamination (hereinafter referred to as the method), developed as a result of the assignment «Development of methods for estimating exposure doses, expected as a result of inhalation intake of radionuclides in emergency situations in territories with a high level of radioactive contamination» activity 1.2 «Reducing the risks of transboundary transfers of radioactive elements in emergency situations in the radioactively contaminated territories of the member states of the Union State and increasing the efficiency of their elimination» of the Program of Joint Activities of Russia and Belarus within the framework of the Union State for the protection of the public and rehabilitation of territories affected by the disaster at the Chernobyl nuclear power plant (hereinafter – the ChNPP) in terms of the responsibility of the Belarusian side. The application of this method will make it possible to assess the volumetric activity of radionuclides in the air during forest fires; committed effective exposure doses to workers as a result of inhalation intake of radionuclides during forest fire extinguishing in areas with a high level of radioactive contamination and expected effective exposure doses to the public from inhalation intake of radionuclides during forest fires in areas with a high level of radioactive contamination. The results of testing the method and a comparative analysis of the results of calculating the inhalation exposure doses of workers and the public obtained using the method with the results of modeling obtained using the JRODOS-Wildfire software module [1] are presented. To assess the consequences of a fire scenario in a section of the Polessky State Radiation-Ecological Reserve (hereinafter – PSRER) with a contamination density of the territory of 137Cs − 3.0–3.7×106 Bq/m2, 90Sr − 9.2×105 Bq/m2, 239Pu − 9.1–12×103 Bq/m2, 241Am − 2.1–2.6×104 Bq/m2 Using the developed method, the values of volumetric activity of radionuclides at the fire site in the workers breathing zone were calculated: for 238Pu − 0,39×10-2 Bq/m3, 239,240Pu − 0,67×10-2 Bq/m3, 241Am − 1,59×10-2 Bq/m3, 90Sr − 0,38 Bq/m3, for 137Cs − 1,03 Bq/m3. The predicted values of inhalation exposure doses of workers will be 1,70×10-6Sv, and inhalation exposure doses of the population living at a distance of 87 km from the fire site (Mozyr city) will be 4,1×10-11 Sv (for adults). The total value of the inhalation exposure dose for a worker who repeatedly extinguished fires in the PSRER in 2019 during the year, calculated using the JRODOS-Wildfire module, was 7,5×10-6Sv/year. All estimated levels of radiation doses do not exceed the established dose limits − 5 mSv and 1 mSv, respectively, and indicate that there is no need to apply special protective measures for workers and the public.